Identification and Characterization of Long Non-coding RNAs in the Intestine of Olive Flounder (Paralichthys olivaceus) During Edwardsiella tarda Infection - Xiu, Yunji; Li, Yingrui; Liu, Xiaofei; Su, Lin; Zhou, Shun; Li, Chao (Frontiers in Immunology, 2021)
Long non-coding RNAs (lncRNAs) play widespread roles in fundamental biological processes, including immune responses. The olive flounder (Paralichthys olivaceus), an important economical flatfish widely cultured in Japan, Korea, and China, is threatened by infectious pathogens, including bacteria, viruses, and parasites. However, the role of lncRNAs in the immune responses of this species against pathogen infections is not well understood. Therefore, in this study, we aimed to identify lncRNAs in the intestines of olive flounders and evaluate their differential expression profiles during Edwardsiella tarda infection, which is an important zoonotic and intestinal pathogen. A total of 4,445 putative lncRNAs were identified, including 3,975 novel lncRNAs and 470 annotated lncRNAs. These lncRNAs had shorter lengths and fewer exons compared with mRNAs. In total, 115 differentially expressed lncRNAs (DE-lncRNAs) were identified during E. tarda infections. To validate the expression pattern of lncRNAs, a total of six DE-lncRNAs were randomly selected for quantitative real-time PCR. The co-located and co-expressed mRNAs of DE-lncRNAs were predicted, which were used to conduct the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. The target genes of DE-lncRNAs enriched numerous immune-related processes and exhibited a strong correlation with immune-related signaling pathways. To better understand the extensive regulatory functions of lncRNAs, the lncRNA–miRNA–mRNA regulatory networks were constructed, and two potential competing endogenous RNA (ceRNA) networks, LNC_001979-novel_171-Potusc2 and LNC_001979-novel_171-Podad1, were preliminarily identified from the intestines of olive flounders for the first time. In conclusion, this study provides an invaluable annotation and expression profile of lncRNAs in the intestines of olive flounders infected with E. tarda; this forms a basis for further studies on the regulatory function of lncRNAs in the intestinal mucosal immune responses of olive flounders.